Impact of Maternal Smoking on Nonsyndromic Clefts: Sex-Specific Associations With Side and Laterality. (February 2021) - Kruse, Teresa; Mangold, Elisabeth; Braumann, Bert
Objective: To compare the incidence of right-sided versus left-sided, and unilateral versus bilateral, nonsyndromic clefting in the affected offspring of smoking and nonsmoking mothers. Design: Self-report data on periconceptual and first trimester smoking behavior were collected from 842 mothers of children with nonsyndromic orofacial clefting. Differences in the incidence of left- versus right-sided clefts, and of unilateral versus bilateral clefts, were analyzed between the children of smoking and nonsmoking mothers. Setting: Interviews and clinical examinations took place at 8 specialist centers in Germany. Patients and Participants: Children with nonsyndromic clefts were recruited during the course of surgical or orthodontic treatment, or within the context of the annual control consultation. Patients with cleft palate only or missing data were excluded. The final cohort comprised 842 patients (540 males and 302 females) with unilateral or bilateral clefts. The respective mothers were interviewed. Main Outcome Measure: Side and laterality of nonsyndromic clefts were the main outcome measures. Results: Children of smoking mothers more often had right-sided clefts than children of nonsmoking mothers (42% right-sided clefts in children of smoking mothers vs 31% of nonsmoking mothers). Children of smoking mothers more often had bilateral clefts than children of nonsmoking mothers (35% bilateral clefts in children of smoking mothers vs 29% of nonsmoking mothers). Sex-specific analyses confirmed substantially and statistically significant associations only for girls. Conclusions: The results suggest that maternal smoking is a sex-specific, exogenous determinant of laterality and side in nonsyndromic clefts.